Long non-coding RNAs enable precise diagnosis and prediction of early relapse after nephrectomy in patients with renal cell carcinoma - Bohosova, Julia; Kozelkova, Katerina; Al Tukmachi, Dagmar; Trachtova, Karolina; Naar, Ondrej; Ruckova, Michaela; Kolarikova, Eva; Stanik, Michal; Poprach, Alexandr; Slaby, Ondrej (Journal of cancer research and clinical oncology, 2023)
PURPOSE: Renal cell carcinoma belongs among the deadliest malignancies despite great progress in therapy and accessibility of primary care. One of the main unmet medical needs remains the possibility of early diagnosis before the tumor dissemination and prediction of early relapse and disease progression after a successful nephrectomy. In our study, we aimed to identify novel diagnostic and prognostic biomarkers using next-generation sequencing on a novel cohort of RCC patients. METHODS: Global expression profiles have been obtained using next-generation sequencing of paired tumor and non-tumor tissue of 48 RCC patients. Twenty candidate lncRNA have been selected for further validation on an independent cohort of paired tumor and non-tumor tissue of 198 RCC patients. RESULTS: Sequencing data analysis showed significant dysregulation of more than 2800 lncRNAs. Out of 20 candidate lncRNAs selected for validation, we confirmed that 14 of them are statistically significantly dysregulated. In order to yield better discriminatory results, we combined several best performing lncRNAs into diagnostic and prognostic models. A diagnostic model consisting of AZGP1P1, CDKN2B-AS1, COL18A1, and RMST achieved AUC 0.9808, sensitivity 95.96%, and specificity 90.4%. The model for prediction of early relapse after nephrectomy consists of COLCA1, RMST, SNHG3, and ZNF667-AS1 and achieved AUC 0.9241 with sensitivity 93.75% and specificity 71.07%. Notably, no combination has outperformed COLCA1 alone. Lastly, a model for stage consists of ZNF667-AS1, PVT1, RMST, LINC00955, and TCL6 and achieves AUC 0.812, sensitivity 85.71%, and specificity 69.41%. CONCLUSION: In our work, we identified several lncRNAs as potential biomarkers and developed models for diagnosis and prognostication in relation to stage and early relapse after nephrectomy.
Keywords: Carcinoma, Renal Cell; Biomarker; nefrektomie; Diagnosis; Long non-coding RNA; Prognosis; lidé; regulace genové exprese u nádorů; Next-generation sequencing; karcinom z renálních buněk; Neoplasm Recurrence, Local; lokální recidiva nádoru; Kidney Neoplasms; Biomarkers, Tumor; nádorové biomarkery; Nephrectomy; Humans; Gene Expression Regulation, Neoplastic; RNA dlouhá nekódující; Early relapse; RNA, Long Noncoding; nádory ledvin